Pediatric dentistry during rooming-in care: evaluation of an innovative project for promoting oral health (Journal of Applied Oral Science, 2004)
According to the current paradigm for promoting health, dental care should be a consideration from the first months of life, or even before birth. The aim of this paper is to evaluate mothers' knowledge of and attitude toward their babies' oral health after receiving guidance during the neonatal period. Forty-six mothers were contacted and asked about the advice they had received and how they felt about the information provided. The mothers recruited for the study were divided into two groups, A (n=25) and B (n=21), according to the time elapsed since their participation in the project, that is, less than or equal to three months and more than three months, respectively. A Wilcoxom rank sum test did not show any statistically significant difference between the two groups (p>;0.05). Guidance on the baby's oral hygiene, breastfeeding the baby exclusively until the sixth month, as well as the restrictions imposed on sugar intake were what the mothers remembered most. Recommendations concerning good arch development and the use of bottles were what mothers remembered least. Regarding infant oral health, it would be advisable to schedule prenatal and neonatal visits, with the second post-natal consultation no later than four months after childbirth.